Understanding Carbon Capture And Storage (Ccs) Potential In Indonesia - Ego Syahrial; Usman Pasarai; Utomo P Iskandar (Scientific Contributions Oil and Gas, 2010)
National energy policy drawn up by the government through Energy Mix Target 2025 (Presidential Regulation No.5/2006) is still dominated by fossil fuel. Moreover, it is coupled with high dependence on fossil fuel, increasing demand of energy and standard of living and high rate population growth, it can turn Indonesia into one of the biggest emitter in the future. On 2009, the government has pledged a non-binding commitment to reduce country emissions by 26% in 2020. This aspiring target requires great efforts besides reliying on current strategies such as energy mix improvements, the switch to less-carbon intensive fuels and renewable resources deployment as well as conservation. Carbon Capture and Storage (CCS) is one of the climate change mitigation tools with the technological capability to reduce CO2 in substantial amount and deep cut particularly on energy sector. CCS is typically defined as the integrated process of CO2 separation at industrial plants, transportation to storage sites and injection into subsurface formations. This paper explains the possibility of CCS potential deployment in Indonesia by reviewing required components and provides comprehensive understanding in each CCS key lements.